Surmonter la crise écologique par un projet spirituel d’ordre supérieur? À partir d’une lecture de Pierre Teilhard de Chardin et de Michel Serres - Hervé Brédif (VertigO)
The comparative reading of works by Michel Serres and Pierre Teilhard de Chardin to think in other terms the ecological crisis, while placing it in the evolution process of life on earth. Although differences exist between these authors, a major convergence can be found: both of them are lead to the idea that humanity and life itself are invited to take a major evolutionary step. It appears that two totalities, Humanity on one hand, Earth-nature on the other hand, now have for common horizon the development of a genuine symbiotic relationship. However, the success of what looks like a higher-level and spiritual project is not guaranteed. Specific conditions are required. Michel Serres underlines the essential change of relations between humankind and the earth as a whole ; he places his hopes in the establishment of a contract between these two global entities. For Teilhard de Chardin, it is of the highest importance that every human being remains convinced that the process will be of benefit to him and not only for a few, the human specie or what could follow her. Instead of using fear and the threat of an imminent disaster, it would be preferable to rely on a higher-level project and the prospects it offers.